Assessment of the half-life of cationic periodontal pocket irrigation - Tugrul Kirtiloglu; Ilker Keskiner; Murathan Sahin; Banu Kirtiloglu; Safak Aygul; Umur Sakallioglu; Gokhan Acikgoz (BMC, 2020)
Abstract Background The concentration and persisting time of antimicrobial agents in the periodontal pockets are important factors for their antimicrobial efficacy. Increased clearance time in the periodontal pocket is a significant criterion for the selection of intrapocket irrigants. The aim of this study was to estimate the clearance time of a cationic agent from the periodontal pocket. Methods Thallium-201(Tl-201) was chosen as a tracer to simulate the clearance of cationic substance because of its electrical activity. Twenty patients with periodontitis and probing depths 6 to 9 mm were included in this study. In each patient, 3 Mega Becquerel (MBq) of Tl-201 were inserted into the periodontal pocket. Dynamic imaging was performed and clearance of radioactivity was measured. Results Clearance of radioactivity was 67.1 ± 16.9, 83.1 ± 13.9, 90.4 ± 10.4, 93.39 ± 8.0% at 30, 60, 90 and 120 min, respectively. Half-life of wash-out was determined as 20.3 ± 10.2 min. Conclusion The results of this study demonstrate that the half-life of the cationic solution applied subgingivally was approximately 20 min and labelling of oral irrigants with radiotracers may be used to determine their clearance in further research.